Artificial Intelligence (AI) trends in higher education learning: Bibliometric analysis - Ai Pemi Priandani; Cepi Riyana; Asep Herry Hernawan; Laksmi Dewi; Mario Emilzoli; Gema Rullyana (Universitas Pendidikan Indonesia, 2025)
The development of artificial intelligence (AI) technology has driven significant transformations in higher education. The integration of AI in learning offers the potential to increase the effectiveness, efficiency, and personalization of data-driven learning. This study aims to conduct a comprehensive bibliometric analysis of AI research trends in higher education learning, tracing publication patterns, source distribution, geographic distribution, and emerging themes in academic literature. The study uses a quantitative descriptive method with bibliometric analysis of Scopus publication data 2018–2023. The analysis was conducted using VOSviewer to map bibliographic relationships between publications, sources, authors, countries, and keywords. The results show that AI publications in higher education have increased rapidly, especially in 2023. The dominant themes are